The Impact of Business Ethics on Employee Engagement: Case Study from the Jordanian Social Security Corporation - Banyhamdan, Khaled Mohammad Talal; Alnajdawi, Sakher; Hanandeh, Rami; Al-Ghalabi, Ruba Risheed; Khaddam, Amineh (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to investigate the impact of business ethics on employee engagement: an empirical study by the Jordanian Social Security Corporation. A simple random sampling technic was use on the target population by distributing 350 questionnaires, 302 questionnaires was valid to analysis. Summing up the results obtained, it has shown that there is a significant positive impact of business ethics on employee engagement. Employee engagement is influenced by business ethics, as business success is strongly influenced by ethics nowadays. The study reveals that the ethical implications of business are at a high level and are more complex than assumed, that ethical behavior brings significant employee output.